Overview of the Tonnidae (MOLLUSCA: GASTROPODA) in Chinese waters - Vos, C. (Shell Discoveries, 2012)
see Vos, C. (2013) Gloria Maris 52(1-2), pp. 22-53
Partial translation into Chinese of English "master" version published in Gloria Maris 52(1-2), Jan. 2013